Rural Development: Sector Policy Paper - world Bank (world Bank (Washington, D. C), 1975)
It is a strategy designed to improve the economic and social life of a specific group of people - the rural poor.
occ 15/01/2019
Loans
Keywords: Rural conditions; Economic assistance; Rural development